203 Data collection/abstraction process improvements to achieve injury-related health equity in our national trauma healthcare system. (5th May 2020) - Conrick, Kelsey; Mills, Brianna; Mohamed, Khadija; St. Vil, Christopher; Rowhani-Rahbar, Ali; Moore, Megan
Abstract : Statement of Purpose: Identifying injury-related disparities requires accurate patient representation. Understanding data collection/abstraction staff perspective is critical to developing implementation models for integrating health equity data elements into electronic medical record (EMR) and trauma registry systems. To identify barriers/facilitators to collecting/abstracting accurate equity data, we assessed perspectives of national stakeholders in each U.S. region and Emergency Department (ED) registration and trauma registry staff locally. Methods: We conducted a Delphi process with 17 national experts in trauma care systems (included based on recommendations from local and national trauma care leaders) and focus groups with 14 ED patient registration and 9 hospital trauma registry staff. Topics included process of data collection/entry into EMR and data abstraction into trauma registries and barriers/facilitators to accurate collection/abstraction of equity data elements. Audio-recorded focus groups and Delphi recommendations were qualitatively analyzed, and the latter findings were joint-ranked based on feasibility scores and Kappa-based score consistency. Findings were triangulated with ED patient registration observations and trauma registry staff workflow. We developed an implementation model addressing identified barriers/facilitators. Results: Delphi results indicated staff time/investment in process changes as the biggest barriers; facilitators were simplicity and brevity (self-report), and quality improvement checks. ED staff barriers included experiences with patients reacting negatively, and misunderstanding data collection purpose. Cultural-sensitivity training, script for explaining importance of equity data collection, and required data entry for a minimum dataset were facilitators. Trauma registry staff barriers involved needing to search notes for information (e.g., injury address/housing status); staff preferred auto-populated and designated EMR discrete fields. Conclusions: Barriers/facilitators identified differed among national stakeholders, ED registration staff, and trauma registry staff. Successful implementation will involve ongoing staff training, opportunities for patient self-report, and frequent quality improvement checks. Significance: Improved data collection and abstraction processes can increase accuracy of equity measures, facilitating better identification of injury-related disparities.